Geteiltes Leid - Sawallisch, Robert (Germany, 2011)
The big Metropolises of the 21st century rot under huge sand deserts and the last survivors find refuge in the ruin of a skyscraper that rises like a lighthouse from this desert. An incurable virus, that resurrects the dead, has driven humanity to the edge of annihilation. In this apocalyptic world moral and ethics are a priceless luxury, but a small boy stands against the madness. A morbid dystopia of a society on the edge of its existence.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films